THE INTERPLAY BETWEEN RELIGION AND POLITICS FROM THE PERSPECTIVES OF AN ETHICIST - PETER OKE OLUSEGUN (International Studies Journal)
The relationship between religion and politics in Nigeria over the years can be considered as a marriage of perceptual harmony and disharmony.  Religion and politics in Nigeria and Africa as a whole are like siamese twins that are very difficult to separate and which in a way are themselves connected to the particular historical and developmental trajectories of individual societies and nations around the world. Religion has generally had a considerable impact on politics in many regions of the world, not just in Africa. There is no doubt that religious beliefs and practices reinforced political power in the same waypoliticalapprehensionspermeated to the heart of the religious domain. Both religious leaders and political leaders are people whose well-being was closely linked to their people's health and welfare. Existing literature on the interplay between religion and politics have engaged the narratives from the standpoint of the influence of ethnic affiliation on politics, psychology of politics, politics and national development with little attention paid to the interconnectivity between religion and politics and the position of an ethicist in the discourse. The dearth of research in this regard gave rise to this study.  For instance, religious beliefs or solidarity in most cases form the main context for political action and political concerns with religious notions determine the nature of a particular group's collective response. Politics is about power, and due to prevalent religious modes of thinking about the world, this power is widely perceived to be spiritual in nature. Qualitative methodwhich has to do with the use of materials relevant to the study will be employed. Recommendations will be made where necessary to all the stakeholders in religious and political matters.